Analisis Upaya Guru dalam Menanamkan Kesantunan Berbahasa Siswa Kelas Rendah di Sekolah Dasar - Izza, Naily Soimatul; Kironoratri, Lintang; Fardani, Much Arsyad (PGSD Universitas Muria Kudus, 2025)
This study aims to describe the efforts of teachers in instilling language politeness in elementary school students. Language politeness is an important part of shaping studentsâ€™ character and social attitudes. This research employs a qualitative approach with a case study method. Data collection techniques were carried out through observation, interviews, and documentation involving teachers and lower-grade students. The study was conducted at SD Muhammadiyah Birrul Walidain Kudus with the subjects being the homeroom teachers of Grade II and Grade III. The data analysis technique used refers to Miles and Hubermanâ€™s concept, which includes data reduction, data display, and conclusion drawing. The results of the study show that teachers play a strategic role in instilling language politeness through lesson planning, the use of teaching modules, role modeling, as well as reinforcement and habituation in daily interactions. Teachers consistently guide students in using polite expressions such as â€œplease,â€ â€œsorry,â€ â€œexcuse me,â€ and â€œthank you,â€ while also instilling values of courtesy in accordance with the maxims of politeness. Through a sustainable approach, students demonstrated improvement in the use of polite language, both in communication with teachers and with peers.